2017
DOI: 10.1177/1091581817745504
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress as a Mechanism Involved in Kidney Damage After Subchronic Exposure to Vanadium Inhalation and Oral Sweetened Beverages in a Mouse Model

Abstract: Kidney diseases have notably increased in the last few years. This is partially explained by the increase in metabolic syndrome, diabetes, and systemic blood hypertension. However, there is a segment of the population that has neither of the previous risk factors, yet suffers kidney damage. Exposure to atmospheric pollutants has been suggested as a possible risk factor. Air-suspended particles carry on their surface a variety of fuel combustion-related residues such as metals, and vanadium is one of these. Van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Our results indicate that exposure to V and consumption of sucrose cause increased levels of 4-HNE expression in all exposed groups, mainly V + S at week 8, as it was reported before but in the kidney with this same animal model. 11 The generation of reactive oxygen species (ROS) is a normal process in the cellular life cycle; however, when an increase in the production of ROS is observed it can alter the cellular metabolism and its regulation, as well as damage of the cellular structures that leads to oxidative stress. This imbalance is often due to a deficiency in antioxidant defenses through deregulation of antioxidant enzyme systems.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that exposure to V and consumption of sucrose cause increased levels of 4-HNE expression in all exposed groups, mainly V + S at week 8, as it was reported before but in the kidney with this same animal model. 11 The generation of reactive oxygen species (ROS) is a normal process in the cellular life cycle; however, when an increase in the production of ROS is observed it can alter the cellular metabolism and its regulation, as well as damage of the cellular structures that leads to oxidative stress. This imbalance is often due to a deficiency in antioxidant defenses through deregulation of antioxidant enzyme systems.…”
Section: Discussionmentioning
confidence: 99%
“…Another research group, using different compounds and doses of vanadium (45 and 90 mg/kg) reported thickening of glomerular basement membrane, pyknotic nuclei, cellular vacuolization, and pyelonephritis [44]. In our group, in a subchronic model of vanadium inhalation, we found foci of inflammatory cells, vacuolation, loss of microvilli of epithelial tubular cells, and changes in urine parameters as proteinuria and hematuria associated to the increase, in a time dependent manner, of 4-hidroxynonenal (4-HNE) [45] ( Figure 1A and B). Oxidative stress is also the toxic vanadium mechanism reported by other groups, for example, Marouane et al [46] found lipid peroxidation, protein denaturation, DNA degradation, and cell membrane disintegration; in addition, Scibior et al [47] reported elevated malonaldehyde (MDA) as a marker of oxidative stress and enhanced total antioxidant status in a rat model of 12-week oral sodium metavanadate exposure.…”
Section: Urinary Systemmentioning
confidence: 64%
“…Direct toxic ingestion: recent research relates ingestion of food ingredientsespecially sugar (sucrose or high fructose) present mostly in sugar-sweetened beverages (SSB)-with tissue damage. Although there is no specific data on gut tissue damage, it has been reported in other bodily systems-e.g., kidney [45]. This represents a particularly severe problem in a world where no matter the country, the SSB consumption increases steadily year after year [57].…”
Section: Digestive Systemmentioning
confidence: 99%
“…Suspended particles containing vanadium are inhaled into the respiratory system and reach the circulation and organs, adversely affecting the individual's physical health [10,11]. Inhalation of air containing vanadium can lead to pathological effects on human organ systems including the respiratory system, lungs, neurological system, eyes, hematopoietic tissue, immune system, and cardiac physiology, potentially through the induction of reactive oxygen species (ROS) and inflammatory responses [10][11][12]. These inhalations studies with mice have demonstrated that the form of vanadium is critical, with some being much more toxic than others [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, high air concentrations of vanadium occur in the occupational setting as a result of the presence of vanadium oxides in dust, leading to humans being exposed to an excessive amount of vanadium, with resulting toxicity. There is growing evidence that inhalation of vanadium-rich environmental pollutions, particularly vanadium pentoxide, can cause damage to human organ systems [10][11][12]. In addition, vanadium pentoxide is classified as possibly carcinogenic to humans by the IARC (International Agency for Research on Cancer).…”
Section: Introductionmentioning
confidence: 99%